Fibroblast Growth Factor 1 Gene and Hypertension: From the Quantitative Trait Locus to Positional Analysis - Tomaszewski, Maciej; Charchar, Fadi J.; Lynch, Mark D.; Padmanabhan, Sandosh; Wang, William Y.S.; Miller, William H.; Grzeszczak, Wladyslaw; Maric, Christine; Zukowska-Szczechowska, Ewa; Dominiczak, Anna F. (Circulation (New York, N.Y.), 2007)
Background— The distal portion of the long arm of chromosome 5 is linked to hypertension and contains functional candidate blood pressure–regulating genes. Methods and Results— Tightening the grid of microsatellite markers under this quantitative trait locus in the Silesian Hypertension Study (629 individuals from 207 Polish hypertensive families) provided enhanced support for linkage of this region to blood pressure (maximal Z =3.51, P =0.0002). The fine mapping, comparative genomics, and functional prioritization identified fibroblast growth factor 1 gene (FGF1) as the positional candidate. Linkage disequilibrium mapping based on 51 single nucleotide polymorphisms spanning the locus showed no overlap between 3 independent haploblocks of FGF1 and the adjacent extragenic chromosomal regions. Single and multilocus family-based analysis revealed that genetic variation within FGF1 haploblock 1 was associated with hypertension and identified a common intronic single nucleotide polymorphism, rs152524, as the major driver of this association ( P =0.0026). Real-time quantitative polymerase chain reaction and Western blotting analysis of renal tissue obtained from subjects undergoing unilateral nephrectomy showed an increase in both mRNA and protein FGF1 expression in hypertensive patients compared with normotensive controls. Renal immunohistochemistry revealed that FGF1 was expressed exclusively within the glomerular endothelial and mesangial cells. Conclusions— Our data demonstrate that genetic variation within FGF1 cosegregates with elevated blood pressure in hypertensive families and that this association is likely to be mediated by upregulation of renal FGF1 expression. The results of our study will need to be replicated in other cohorts.